Lessons from the Aral Sea disaster and rational solutions for future generations - Abdurakhmonovich , Azizkulov Akram (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the historical trajectory of the Aral Sea disaster and examine its ecological, social, and economic consequences. The research highlights how the drying up of the Aral Sea has affected environmental security, public health, and the livelihoods of surrounding communities. Research methodology: The article employs a qualitative historical-analytical approach, using secondary data from scientific publications, government reports, and international organizations. Comparative analysis is applied to evaluate environmental, socio-economic, and policy dimensions, while a conceptual framework of sustainable development guides the assessment of possible solutions. Results: Findings reveal that the degradation of the Aral Sea has caused severe ecological imbalance, including biodiversity loss, desertification, and water scarcity. Socially, local populations face deteriorating health conditions due to dust storms and polluted water, while economically, agriculture and fisheries have collapsed, leading to unemployment and migration. At the same time, international cooperation and the application of innovative technologies are identified as potential drivers of regional recovery. Conclusions: The Aral Sea disaster represents one of the most significant ecological crises of the twentieth century, with lasting impacts on future generations. Restoration requires integrated strategies combining cross-border collaboration, environmental innovation, and sustainable resource management. Limitations: The study is limited by reliance on secondary data and the absence of primary field research, which may restrict contextual depth and recent local perspectives. Contribution: This article offers insights and recommendations, stressing sustainable strategies to restore the Aral Sea and ensure environmental security.